VIDEO DIGITAL STORYTELLING BERBANTUAN BONEKA TANGAN PADA CERITA DONGENG KELAS 4 SEKOLAH DASAR - Rita Sundari; Dwi Agus Setiawan; Denna Delawanti Chisyarani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The lom ability of students to understand and reconstruct fairy tales indicates the need for inovation in indonesian language learning media. The use of convetional methods makes students less active and makes it difficult to grasp the content and moral messages of the story . This study aims to develop a digital storytelling video media assisted by hand puppets that is feasible, partical, and effective for use in learning, especially to support students ability to retell the story and explore moral values. The study was conducted at SDN Tanjungrejo 1 Malang with 23 fourth-grade students as subjects, using qualitative and quantitative data approaches through the ADDIE Research and Development (R&D) model. The instruments used incluced expert validation sheets, teacher and student response questionnaires, observastion sheets, and pretests and postets. The product was developed in the form of a video entitled “Lyli Yang Sombong”, with hand puppet characters, presented in an attractive manner and uploaded on the Youtube platfrom for easy access. The validation results from material, languange, and media experts showed an average feasibility of 88,33% (feasible category). Field trials showed an increase in students active participation in learning. Students were more attentive, built imagination, and created emotional connections with the story characters. The pretest and posttest results showed significant results, with an average N-Gain of 0,81 (high category). Particality was also high, with teacher responses of 85% and 90% respectively. Thus, this medium has proven to be feasible, partical, and effective in teaching storytelling in elementary schools.